INVESTIGATION OF PROCESS PERTAINING TO INTERACTION OF TRACTOR DRIVING WHEELS WITH GROUND SURFACE - V. V. Guskov; A. A. Dzioma; A. S. Kolola; R. Yu. Makarenko; N. I. Zezetko (Наука и техника)
The paper presents results of investigations on the process pertaining to interaction of a driving wheel with ground surface and describes methodology for optimization of backbone parameters. The mentioned process has some specific differences in comparison with the process of wheel rolling along hard surface. Ground surface is represented by mixture of sandy and clay particles with plant residues and it has a number of physical and mechanical properties. The main of these properties is resistance of soil against compression and displacement. Compression process determines a track depth and resistance to motion and displacement process determines wheel gripping property and its tangential traction force. While executing the investigations laws of compression and displacement proposed by Prof.V. V. Katsygin as the most adequate reflection of actual processes have been used in the paper. Motion of the driving wheel along ground surface is accompanied by its slipping. It has been determined that the maximum wheel traction force is formed not with 100% slipping as it was supposed until present but the value has been obtained at 45–60 % slipping according to soil category. The developed integral equations with due account of the aspect make it possible to calculate road hold characteristics of driving wheels of the designed wheel tractor and evaluate its traction, speed and economic characteristics. Methodology has been developed for optimization of backbone parameters of wheeled running gear in the designed tractor such as design mass and adhesion weight, width, diameter and air pressure in a tire. The proposed methodology has been introduced in designing practice of wheeled tractors at OJSC “Minsk Tractor Works”.